2010
DOI: 10.1007/s00408-010-9270-3
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Airway Disease and Obstructive Sleep Apnea: Effect of Pulmonary Function

Abstract: This study sought to determine whether reduced pulmonary function in obstructive airway disease (OAD) is an independent risk factor for obstructive sleep apnea (OSA). This was a prospective observational study conducted at an outpatient pulmonary clinic. Adults with a known diagnosis of COPD/asthma were enrolled as OAD group. Family members without a history of COPD/asthma who accompanied these patients to the clinic were enrolled as a control group. The Berlin Questionnaire (BQ) was used to assess OSA risk in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 22 publications
6
41
0
3
Order By: Relevance
“…However, because those with a BP were, on average, 13 years older than those without a BP, the higher incidence of BPs in the severe OSA group may have been confounded by age. Our data suggest that age is a significant contributor to the presence of a BP in quiet breathing and, although we do not have polysomnography tests for OSA in our participants, our OSA risk data, which is a good predictor of OSA (Sharma et al ., ), suggests that, similar to COPD, OSA did not play a part in BP incidence.…”
Section: Discussionmentioning
confidence: 92%
“…However, because those with a BP were, on average, 13 years older than those without a BP, the higher incidence of BPs in the severe OSA group may have been confounded by age. Our data suggest that age is a significant contributor to the presence of a BP in quiet breathing and, although we do not have polysomnography tests for OSA in our participants, our OSA risk data, which is a good predictor of OSA (Sharma et al ., ), suggests that, similar to COPD, OSA did not play a part in BP incidence.…”
Section: Discussionmentioning
confidence: 92%
“…However, the authors studied a community sample of patients with mild subclinical disease, and thus the findings may not generalize to clinical cohorts. On the other hand, Sharma and coworkers found a high risk of OSA in patients with COPD, but the authors failed to use gold standard polysomnography, and thus the results may be biased by misclassification (45).…”
Section: Discussionmentioning
confidence: 99%
“…The mean duration of the OSA symptoms before the diagnosis in these patients was made at 20 months. We have previously shown that OSA is an under-diagnosed co-morbidity in COPD patients (27). This is important, because CPAP treatment has been shown to reverse pulmonary hypertension in OSA (8), and even reduce COPD-exacerbation related hospitalizations and mortality in patients with the overlap syndrome (4).…”
Section: Discussionmentioning
confidence: 99%